Simulation and Process Optimization of a Membrane-Based Dense Gas Extraction Using Hollow Fiber Contactors - Cubillos-Montecino, F; Romero-Figueroa, J; Estay-Cuenca, H (2012)
Supercritical fluid and membrane technology coupling is a relatively new concept applicable to solvent separation and solute extraction. In these processes a hydrophobic or hydrophilic macroporous membrane is used as a two-different-nature solutions contactor. This methodology is an alternative to conventional liquid solution supercritical fluid extraction processes, which are associated with high investment costs. In the present work, a membrane-based supercritical fluid extraction module is modeled, simulated, and optimized as an independent industrial-scale operational unit. UniSim design suite R390 software from Honeywell was used as the platform for the simulation. Acetone and ethanol literature extraction results and methanol experimental extraction results (27.6% to 14.5% with a 10 wt.% aqueous solution; 7.1% to 5.9% with a 500 ppm aqueous solution) were used for validation of the model and definition of the semi-empirical equation parameters. The generated industrial-scale system optimization, which used a modular membrane arrangement, was strongly dependent on thermodynamic, economic, and energetic variables (higher mass transfer resistance in the carbon dioxide phase increased the number of membranes needed; process feasibility was affected by the number of membrane units, carbon dioxide flow rate, and product added value; compression energy requirements affected the optimization result). The modeled system proved to be an important aid in the design, scaling, and optimization of systems that use membranes as phase contactors in liquid solution supercritical carbon dioxide extraction. © 2012 Taylor and Francis Group, LLC.